Exploiting Aromatic Interactions for β‐Peptide Foldamer Helix Stabilization: A Significant Design Element. Issue 16 (24th March 2014) - Mándity, István M.; Monsignori, Antonella; Fülöp, Lívia; Forró, Enikö; Fülöp, Ferenc
Abstract Tetrameric H10/12 helix stabilization was achieved by the application of aromatic side‐chains in β‐peptide oligomers by intramolecular backbone–side chain CH–π interactions. Because of the enlarged hydrophobic surface of the oligomers, a further aim was the investigation of the self‐assembly in a polar medium for the β‐peptide H10/12 helices. NMR, ECD, and molecular modeling results indicated that the oligomers formed by cis‐[1S, 2S]‐ or cis‐[1R, 2R]‐1‐amino‐1, 2, 3, 4‐tetrahydronaphthalene‐2‐carboxylic acid (ATENAC) and cis‐[1R, 2S]‐ or cis‐[1S, 2R]‐2‐aminocyclohex‐3‐enecarboxylic acid (ACHEC) residues promote stable H10/12 helix formation with an alternating backbone configuration even at the tetrameric chain length. These results support the view that aromatic side‐chains can be applied for helical structure stabilization. Importantly, this is the first observation of a stable H10/12 helix with tetrameric chain‐length. The hydrophobically driven self‐assembly was achieved for the helix‐forming oligomers, seen as vesicles in transmission electron microscopy images. The self‐association phenomenon, which supports the helical secondary structure of these oligomers, depends on the hydrophobic surface area, because a higher number of aromatic side‐chains yielded larger vesicles. These results serve as an essential element for the design of helices relating to the H10/12 helix. Moreover, they open up a novel area for bioactive foldamer construction, while the hydrophobic area gained through the aromatic side‐chains may yield important receptor–ligand interaction surfaces, which can provide amplified binding strength.